POLA PERMUKIMAN NEOLITIK DI KAWASAN DANAU GRATI KABUPATEN PASURUAN, JAWA TIMUR - Kasnowihardjo, Gunadi (BRIN, 2012)
Study of Neolithic settlement pattern in Ranu Grati area at Pasuruan-East Java is a part of research series on the ancient settlements at the lakes area in East Java, conducted by author since 2008. Research has been csttied out every year in a row starting from Ranu Klakah, Ranu Gedang, Ranu Segaran, Ranu Bethok, and Ranu Grati. Eventhough in its early stage of research, the results are quite promising, both geoarchaeological and archaeological landscape as well as its artifactual data. Lake terraces as geo-archaeological data and artifacts such as pottery sherds, net-sinkers, and Neolithic adze are evidences of settlement in Grati Lake area.